Cost-effectiveness analysis of quadrivalent versus trivalent influenza vaccine in Taiwan: A lifetime multi-cohort model - Ming-Chin Yang; Elise Chia-Hui Tan; Jian-Jhih Su (Taylor & Francis Group, 2017)
A government-funded trivalent influenza vaccine (TIV) program to prevent seasonal influenza was implemented in Taiwan since 1998. However, mismatch between the vaccine and circulating strains may occur. Alternatively, a quadrivalent influenza vaccine (QIV) includes all 4 influenza lineages could minimize the risk of mismatches. Therefore, QIV could be considered as an alternative strategy to enhance protection against seasonal influenza. The objective of the study was to analyze, from a governmental perspective, the cost-effectiveness of using QIV vs. TIV as a vaccination strategy in Taiwan. A lifetime multi-cohort, static Markov model was constructed with 9 age groups to assess the costs and effectiveness of QIV vs. TIV. Direct costs were obtained from a database released by the Ministry of Health and Welfare. Outcomes included life-years gained, quality-adjusted life years (QALYs) gained, influenza cases avoided and incremental cost-effectiveness ratios (ICERs). The discount rate of costs and effectiveness was set at 3.5% and the time horizon used in the model was 100 y. Results show that a vaccination strategy utilizing QIV instead of TIV would bring an additional 10,557 QALYs at an extra cost of US$39.4 million, yielding an ICER of US$3,015.07 per QALY gained. When setting the willingness-to-pay threshold at US$10,000, compared to TIV, the probability that QIV would be cost-effective was 98%. Sensitivity analyses show that ICER was sensitive to the changes of circulation of influenza virus subtypes and vaccine mismatch. From a governmental perspective, the QIV vaccination could be considered as a cost-effective strategy within the context of public health in Taiwan.